Bovine Viral Diarrhea (BVD) - Eddie J. Richey (EDIS, 2004)
The bovine viral diarrhea virus (BVDV) is a widespread problem for beef and dairy herds. BVDV can readily cross into other species, such as sheep, goats, deer, antelope and bison. However, I will confine my remarks to BVDV in cattle. I will further shorten the discussion by referring to the virus and the disease(s) it causes as bovine viral diarrhea (BVD). This document is VM121, one of a series of the Veterinary Medicine-Physiological Science Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date December 10, 2004.